Pendampingan Budidaya Talas Varietas Baru Bagi KWT Sawargi Kelurahan Situgede Kecamatan Bogor Barat Kota Bogor - Febi Nurilmala; Andi Masnang; Nia Sonani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The continuity of the availability of raw materials for the processing of taro is a partner's need to develop a taro processing business, so that appropriate technology is needed for the cultivation of the new variety Febi521 taro. The service programme offered to KWT Sawargi is the use of narrow land owned by KWT members to plant the new Febi521 variety of taro, and it is hoped that it will continue so that the difficulty of taro raw materials can be overcome. Community service activities were carried out for 10 months consisting of training in new varieties of taro cultivation, the practise of planting Febi521 taro seeds and assistance until harvest. The results of this activity had a positive impact on the people of Situ Gede Village, especially KWT Sawargi. The taro seeds planted in the fields of several partners showed that the plants grew to a harvest of 83.33%. Febi521 taro is harvested at around 8 months of age and produces a weight of 76 kg from 100 plants with a weight of 500 - 800 grams per tuber. Assistance will continue to be provided until the partner becomes an independent KWT.